2022
DOI: 10.3389/fimmu.2022.1030610
|View full text |Cite
|
Sign up to set email alerts
|

Histones: The critical players in innate immunity

Abstract: The highly conserved histones in different species seem to represent a very ancient and universal innate host defense system against microorganisms in the biological world. Histones are the essential part of nuclear matter and act as a control switch for DNA transcription. However, histones are also found in the cytoplasm, cell membranes, and extracellular fluid, where they function as host defenses and promote inflammatory responses. In some cases, extracellular histones can act as damage-associated molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 139 publications
(183 reference statements)
0
34
0
Order By: Relevance
“…The results showed that patient survival was significantly worse in groups with higher clearance rates of heat shock protein 70 and HMGB1. Moreover, growing evidence also shows that histones may exert an antimicrobial activity by binding to bacterial nucleic acids and lipopolysaccharides, changing the permeability of the bacterial cell membrane, and inhibiting viral binding and thus playing a vital role in host innate immunity [ 113 ]. Therefore, further clinical studies are urgently needed to determine the thresholds of plasma HMGB1 and histone levels for initiating, monitoring or discontinuing EBP with a balanced immunomodulation effect on the innate and adaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that patient survival was significantly worse in groups with higher clearance rates of heat shock protein 70 and HMGB1. Moreover, growing evidence also shows that histones may exert an antimicrobial activity by binding to bacterial nucleic acids and lipopolysaccharides, changing the permeability of the bacterial cell membrane, and inhibiting viral binding and thus playing a vital role in host innate immunity [ 113 ]. Therefore, further clinical studies are urgently needed to determine the thresholds of plasma HMGB1 and histone levels for initiating, monitoring or discontinuing EBP with a balanced immunomodulation effect on the innate and adaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies suggest that AAT may also inhibit the NE-mediated degradation of antimicrobial proteins, such as airway-secreted SPLUNC1 ( 49 ), immunoglobulins, and defensins ( 50 ). Histone, which is largely studied in an epigenetic context, is often overlooked in regards to their antimicrobial functions and even more so in their impact in AATD infections ( 51 ). NE has been shown to decrease the cytotoxicity of histone in NET clumps, but its impact on the antimicrobial potency of NETs has not been systematically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the S100s proteins are recognized by TLRs or RAGE, the receptor for advanced glycation end-products [ 18 ]. HMGB1 interacts with RAGE and several TLRs (TLR2, TLR4, and TLR9) depending on the cell types [ 19 ], the histones react with TLR2, TLR4, or TLR9, histone H4 is recognized by the TLR4/MD2 heterodimer, and the nucleosome, which is the histone-DNA complex, is the TLR9-specific ligand [ 20 ]. The recognition of tumor-derived DAMPs therefore usually initiates the activation of signaling cascades, thus leading to sterile inflammation, which forms a reinforcing loop of tumorigenesis.…”
Section: Innate Immune Defence and Tumorigenesismentioning
confidence: 99%